A Multi-Centre Study to Evaluate Method Dependency of the International Sensitivity Index of Bovine Thromboplastin - Peters, R H M; van den Besselaar, A M H P; Olthuis, F M F G (Thrombosis and Haemostasis, 1989)
In The Netherlands, a particular coagulometer method for prothrombin time (PT) determination with reduced sample and reagent volumes is used by 62% of the laboratories controlling oral anticoagulant therapy. This “micro-method” has been calibrated against the manual tilt-tube technique for PT determination by six Dutch laboratories. Each laboratory tested 20 fresh normal blood samples and 60 fresh patient blood samples using both methods with the same batch of bovine thromboplastin reagent, according to a detailed protocol. Both methods were comparable as to their precision, but PTs measured by the micromethod were significantly prolonged (p <0.001, Student’s t-test) as compared to the manual method. This effect is stronger for samples of normal subjects than for patients’ samples. It was assumed that the International Sensitivity Index (ISI) of the bovine thromboplastin for the manual method was 1.00 in each laboratory. The ISI-values of the bovine thromboplastin for the micro-method determined by the six laboratories ranged from 1.00 to 1.07 (mean 1.03, SD 0.03). Our results indicate that any other laboratory, using this thromboplastin and the micromethod, should obtain accurate assessment of the International Normalized Ratio from their own mean normal PT and an ISI which is 3% higher than the ISI supplied by the thromboplastin manufacturer for the manual tilt-tube method.
Keywords: International Sensitivity Index; International Normalized Ratio; Oral anticoagulant control; Prothrombin time